Preeclampsia in Ghana: A study on the prevalence and risk factors of postpartum readmission in the Ashanti Region - Enoch Odame Anto; Wina Ivy Ofori Boadu; Lovelace Kwaku Gyamfi; Emmanuel Ekow Korsah; Ezekiel Ansah; Joseph Frimpong; Valentine Christian Kodzo Tsatsu Tamakloe; Augustine Tawiah; Elizabeth Aboagye; Albright Etwi‐Mensah; Agartha Odame Anto; Christian Obirikorang (Wiley, 2024)
Abstract Background Despite significant improvements in its management, preeclampsia continues to be one of the frequent causes of postpartum readmission. Increased awareness of the risk factors for postpartum readmission is required to reduce its incidence and related complications. This study determined the prevalence and associated risk factors for postpartum readmission among women with preexisting preeclampsia in a Ghanaian population. Methods This hospital‐based retrospective study was conducted at the obstetrics and gynaecology units of Komfo Anokye Teaching Hospital in Ghana. We reviewed the medical records including sociodemographic and obstetric characteristics of preeclampsia patients. Statistical analyses were performed using Statistical Package for Social Sciences Version 26.0 and GraphPad Prism version 8.0. p‐Value <0.05 was considered statistically significant. Results A total of 208 preeclampsia patients were considered in this study. The rate of postpartum readmission for a hypertensive disorder among women with preeclampsia was 46%. After adjusting for multiple confounders in the multivariate logistic model, having a family history of hypertension [aOR = 3.512, 95% CI (1.669-7.394), p = 0.0028] was associated with increased odds for postpartum readmission. However, being nulliparous [aOR = 0.321, 95% CI (0.116-0.887), p = 0.0028] was independently associated with a reduced odd for postpartum readmission. Conclusion The rates of postpartum readmission are significantly high among preeclampsia women. Our findings highlight the importance of continued efforts to improve the health outcomes of both mother and newborn, including heightened monitoring of at‐risk patients in the Ghanaian population.